1994
DOI: 10.1007/bf00043870
|View full text |Cite
|
Sign up to set email alerts
|

The phytochrome apoprotein family inArabidopsis is encoded by five genes: the sequences and expression ofPHYD andPHYE

Abstract: Two novel Arabidopsis phytochrome genes, PHYD and PHYE, are described and evidence is presented that, together with the previously described PHYA, PHYB and PHYC genes, the primary structures of the complete phytochrome family of this plant are now known. The PHYD- and PHYE-encoded proteins are of similar size to the other phytochrome apoproteins and show sequence similarity along their entire lengths. Hence, red/far-red light sensing in higher plants is mediated by a diverse but structurally conserved group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
453
1
7

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(481 citation statements)
references
References 47 publications
20
453
1
7
Order By: Relevance
“…To explore this hypothesis, we used a genetic approach to test whether phytochrome activity is required for SD axillary flower formation. There are at least five phytochrome genes in Arabidopsis (PHYA to PHYE; Sharrock and Quail, 1989;Clack et al, 1994). The activities of all five genes are strongly suppressed by the hy7 mutation that blocks phytochrome chromophore biosynthesis (Parks and Quail, 1991).…”
Section: Control Of Ap2-7 Axillary Flower Production By Phytochromementioning
confidence: 99%
“…To explore this hypothesis, we used a genetic approach to test whether phytochrome activity is required for SD axillary flower formation. There are at least five phytochrome genes in Arabidopsis (PHYA to PHYE; Sharrock and Quail, 1989;Clack et al, 1994). The activities of all five genes are strongly suppressed by the hy7 mutation that blocks phytochrome chromophore biosynthesis (Parks and Quail, 1991).…”
Section: Control Of Ap2-7 Axillary Flower Production By Phytochromementioning
confidence: 99%
“…Phytochromes are soluble chromoproteins that convert photoreversibly between two spectrally distinct forms when sequentially absorbing red (R) and far-red (FR) light, and this interconversion occurs immediately both in vivo and in vitro (Butler et al, 1959). Phytochromes are encoded by a small gene family (phytochrome genes PHYA to PHYE in Arabidopsis; Sharrock and Quail, 1989;Clack et al, 1994). Studies with mutants deficient in specific phytochromes have shown that phytochrome A (PhyA) and phytochrome B (PhyB) have distinct action spectra for the photoinduction of seed germination (Shinomura et al, 1996) and distinct fluence and wavelength requirements for expression of the chlorophyll a / b binding protein gene ( CAB ) (Hamazato et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Active Pfr form can be converted back to the inactive Pr form by absorption of specific far-red light (9,10). The model plant, Arabidopsis thaliana, contains five genes (PHYA to PHYE) that encode phytochrome apoproteins (11,12). Phytochromes are classified as light labile phytochrome A (phyA) and light stable phytochromes B E (phyB-phyE) (13).…”
mentioning
confidence: 99%